UNDEREMPLOYMENT AND WORKERS’ DESKILLING: THE NIGERIAN EXPERIENCE - Ikeije, U. U.; Nwakanma, C. H. A.; Johnpedro, M. I. (UDS International Journal of Development, 2022)
This paper analyzed the Nigerian labour market experience in relation to underemployment and its linkage to workers’ deskilling. The paper adopted the desk review approach by relying on existing data on underemployment from the official records of the accredited government agency (National Bureau of Statistics) saddled with the responsibility of keeping such data. Other supportive data were generated from the International Labour Organization (ILO). The secondary data (which are purely descriptive) from the official records of this agency and international institution were presented, analyzed and used as the basis for explanation of the phenomenon of underemployment and its linkage to workers’ deskilling. The result showed that out of the 72.90% workers who were employed in the 2nd quarter of 2020, 28.57% were underemployed. Another 22.8% represent the underemployed workers out of 66.72% of people engaged in working activities in the 4th quarter of 2020. The paper concludes that a significant percentage of workers in the Nigerian labour market are in jobs that under-utilize their training, skill and technical know-how, and that underemployment as observed in the Nigerian labour market is linked to workers’ deskilling. However, the paper recommends that the labour market operators should embark on retraining and reskilling the affected workers. This could serve as a panacea to deskilling, especially in the short-run.Keywords: Underemployment, Workers’ deskilling, Labour market, Skill underutilization, Nigeria